Trauma-informed initial teacher education training: A necessary step in a system-wide response to addressing childhood trauma - L’Estrange, Lyra; Howard, Judith (Frontiers in Education, 2022)
The growing prevalence of students affected by complex trauma, and the significant implications of unresolved trauma for these students later in life, highlights the imperative for a system-wide response to address the effects of complex trauma in student populations. An important step in this system level response is increasing the knowledge of pre-service teachers in trauma-informed education practice through initial teacher education programs. Trauma-informed education settings are increasingly being recognised as critical in the resolution of complex trauma for impacted learners, however trauma-informed training in preservice teacher education is lacking. While a small body of recent research has shown promise in increasing pre-service teacher knowledge and confidence in teaching children and young people affected by complex trauma, there is scant longitudinal data that informs us of how preservice teachers may be implementing the knowledge they have learnt in their practice after they have graduated. Through survey data, the current study explored the perceptions of 124 Australian pre-service teachers’ knowledge, self-efficacy, and resilience related to working with trauma-affected students before and after completing a six-week initial teacher education unit in managing student behaviours related to complex trauma, and one year after graduating. Key findings indicated preservice teachers’ knowledge, self-efficacy, and resilience in teaching students with complex trauma increased dramatically from pre- to post- study of the six-week unit and this learning continued to be evident one year into their teaching career. However, the data also suggest that these attributes are not something that develops quickly or without ongoing professional learning and practice. Although pre-service and early career teachers seem keen to advance their trauma-awareness, it is important they receive ongoing support to develop their skills into their early careers. These findings have implications for the design of trauma-informed initial teacher education and the importance of additional early career professional learning.